Susceptibility of Populus balsamifera to Septoria musiva A Field Study and Greenhouse Experiment - LeBoldus, Jared M (Plant disease, 2009)
A greenhouse inoculation experiment and field study were conducted to determine the cause of an outbreak of Septoria musiva cankers on Populus balsamifera in a northern Alberta plantation. Four clones of P. balsamifera, five clones of putatively resistant P. deltoides, and one susceptible hybrid poplar clone, Northwest, were inoculated with seven isolates identified as S. musiva. Four of the isolates were from P. balsamifera in Alberta and the others were from P. deltoides in Quebec. Results indicated that disease severity was similar for Alberta and Quebec isolates (P = 0.243) and that P. balsamifera had the greatest mean disease severity (x-bar = 4.20), P. deltoides had the lowest (x-bar = 2.76), and Northwest was intermediate (x-bar = 3.45). A genetic analysis comparing six polymorphic polymerase chain reaction restriction fragment length polymorphism loci and the mitochondrial small subunit ribosomal DNA sequences of the seven isolates indicated that the Alberta population was made up of at least three distinct genotypes. Canker incidence and age on Northwest and 56 different clones of P. balsamifera in a plantation were recorded. Canker incidence (P = 0.726) and the canker age distributions (P = 0.994) were similar for the two species. In conclusion, contrary to what has been reported in the literature, P. balsamifera appears to be quite susceptible to Septoria canker